Resilience of farmers at water shortage situations in minor irrigation systems: a case study in Kurunegala District, Sri Lanka - Wijekoon, W.M.S.M.; Gunawardena, E.R.N.; Aheeyar, Mohamed M. M. (2018)
Farmers in Minor Irrigation Systems (MIS) experience many difficulties due to severe seasonal or year-round absolute water scarcity that affects their livelihoods. In order to address this problem, the resilience of the vulnerable communities needs to be enhanced through smart investments and appropriate adaptation strategies. Since there is no well-established method for assessing the resilience of the farmers in MIS, this study was aimed to develop a framework and prospective methodology to assess resilience and factors determining the resilience to shocks and stresses of MIS. A structured questionnaire survey was carried out among 188 households belong to eight farmer organizations under 16 MIS located in three Agrarian Service Divisions in the IL3 agro-ecological region in Kurunegala District. The resilience of farming was measured using adaptive capacity or the risk management strategies used at household levels related to farming practices using 20 indicators. Analysis of factors was performed with the principle component method and rotated (from Varimax with Kaiser Normalization technique) factor loadings were extracted to compute resilience index. Using the empirical equation derived from the study, the resilience of MIS was quantitatively determined. The results showed that there is an adequate space to enhance the resilience of farming in MIS by introducing and adapting various risk management strategies. It appears that capacity of the tank, accessibility of services and the trust of farmers both on farmer organizations and the agency officials are some of the key factors which govern the resilience of farming in MIS.